Stimulation of Inducible Nitric Oxide by Hepatitis B Virus Transactivator Protein HBx Requires MTA1 Coregulator - Bui-Nguyen, Tri M. (American Society for Biochemistry and Molecular Biology, 2010)
Nitric oxide has been implicated in the pathogenesis of inflammatory disorders, including hepatitis B virus-associated hepatocellular carcinoma. Transactivator protein HBx, a major regulator of cellular responses of hepatitis B virus, is known to induce the expression of MTA1 (metastasis-associated protein 1) coregulator via NF-κB signaling in hepatic cells. However, the underlying mechanism of HBx regulation of the inducible nitric-oxide synthase (iNOS) pathway remains unknown. Here we provide evidence that MTA1 is a positive regulator of iNOS transcription and plays a mechanistic role in HBx stimulation of iNOS expression and activity. We found that the HBx-MTA1 complex is recruited onto the human iNOS promoter in an NF-κB-dependent manner. Pharmacological inhibition of the NF-κB signaling prevented the ability of HBx to stimulate the transcription, the expression, and the activity of iNOS; nevertheless, these effects could be substantially rescued by MTA1 dysregulation. We further discovered that HBx-mediated stimulation of MTA1 is paralleled by the suppression of miR-661, a member of the small noncoding RNAs, recently shown to target MTA1. We observed that miR-661 controls of MTA1 expression contributed to the expression and activity of iNOS in HBx-expressing HepG2 cells. Accordingly, depletion of MTA1 by either miR-661 or siRNA in HBx-expressing cells severely impaired the ability of HBx to modulate the endogenous levels of iNOS and nitrite production. Together, these findings reveal an inherent role of MTA1 in HBx regulation of iNOS expression and consequently its function in the liver cancer cells.